Increasing Knowledge About the Utilization of Public Health Insurance with Education RW 11 Jayagiri Village, Lembang District, West Bandung Regency - Imelda MG Sianipar; Tri Ardayani; Reynaldi Tresnajaya; Anni Sinaga; Treesia Sujana; Wintari Hariningsih (Asosiasi Profesi Multimedia Indonesia, 2024)
The community service aim to increase public understanding of the importance of health insurance. The implementation of activities carried out in August-October consists of preparation, implementation and closing which is carried out in the community in RW 11 of Jayagiri Village. Jayagiri Village is located in Lembang District, West Bandung Regency. The target number of community service activities is 40 people, consisting of elements: Jayagiri Village community, especially in RW 11, health cadres, and village governments and related agencies. The result of the analysis showed that before the implementation of counseling, only 54% of the public understood about health insurance and after counseling it rose to 63%, or an increase of 9%. The number of respondents was 29 people, with answers considered valid amounting to 28 respondents. It can also be seen below public understanding of health insurance increased by 7%, understanding of the components of health insurance increased by 11%, thus significantly encouraging understanding of health insurance by 25%. It also boosted public understanding of the risks in life which increased quite sharply by 21%. By having enough information about health insurance, people are better able to maintain health, prevent disease, and use preventive services provided by health insurance programs. Proper information about health insurance helps people understand the level of financial protection they have in relation to health care costs, so they can avoid unwanted financial surprises and better manage their family budgets.